The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18203/2349-3259.ijct20162795
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between high dose hyperbaric Bupivacaine (12.5 mg) alone versus low dose hyperbaric Bupivacaine (7.5 mg) with Fentanyl (25 µg) in spinal anaesthesia for inguinal hernia surgery

Abstract: <p class="abstract"><strong>Background:</strong> For performing inguinal hernia surgeries, giving spinal anesthesia is a well known technique as it easy and provides fast onset, effective sensory and motor blockade in an awake patient. Now-a-days Bupivacaine is gaining importance as an effective spinal anaesthetic agent in combination with opioid analgesic Fentanyl to reduce the postoperative pain and side effects associated with surgery. This study aims to compare the effectiveness of intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…There were no incidences of vomiting. There was no respiratory depression among the three study groups which was in accordance with the studies of Belzarena et al, 30 Singh et al, 3 Ben David et al 4 and Kotwani et al 31 Itching was significantly seen in patients receiving 25mcg of fentanyl (p value<0.05) which was also seen in the study conducted by Hunt et al, 1 Belzarena et al, 30 Ali et al 11 The incidence of side effects except hypotension were more commonly seen in group using 25 mcg of fentanyl. The strength of the study is that this study is one of the few studies which compared the effect of three doses (15 mcg, 20 mcg, 25 mcg) of fentanyl as an adjuvant with bupivacaine heavy (7.5 mg) as local anaesthetic during spinal anaesthesia for caesarean section.…”
Section: Discussionsupporting
confidence: 90%
“…There were no incidences of vomiting. There was no respiratory depression among the three study groups which was in accordance with the studies of Belzarena et al, 30 Singh et al, 3 Ben David et al 4 and Kotwani et al 31 Itching was significantly seen in patients receiving 25mcg of fentanyl (p value<0.05) which was also seen in the study conducted by Hunt et al, 1 Belzarena et al, 30 Ali et al 11 The incidence of side effects except hypotension were more commonly seen in group using 25 mcg of fentanyl. The strength of the study is that this study is one of the few studies which compared the effect of three doses (15 mcg, 20 mcg, 25 mcg) of fentanyl as an adjuvant with bupivacaine heavy (7.5 mg) as local anaesthetic during spinal anaesthesia for caesarean section.…”
Section: Discussionsupporting
confidence: 90%
“…Majority of researchers have reported incidence ranging from 0%-35% in low dose group and higher incidence of 41% in patients where higher dose of local anaesthetic use. [1,2,9,12,13,18] The other side effects like pruritits, nausea and shivering were not observed in any of the patients unlike other studies where few side effects were reported with the use of opioid adjuvant. [1,6,7,9,12,17] Thus the study highlighted the adequacy of sensory and motor blockade of more than 2 hrs duration with lower incidence of hypotension and vasopressor use there by proving the efficacy of 7.5 mg bupivacaine with fentanyl for better patient outcomes.…”
Section: Discussionmentioning
confidence: 58%
“…[1,2,9,12,13,18] The other side effects like pruritits, nausea and shivering were not observed in any of the patients unlike other studies where few side effects were reported with the use of opioid adjuvant. [1,6,7,9,12,17] Thus the study highlighted the adequacy of sensory and motor blockade of more than 2 hrs duration with lower incidence of hypotension and vasopressor use there by proving the efficacy of 7.5 mg bupivacaine with fentanyl for better patient outcomes. Hence the results can be extrapolated to other surgery of this duration in elderly (like inguinal surgery, fractures etc)…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations